Whole-Genome Sequencing of Clinically Isolated Carbapenem-Resistant Enterobacterales Harboring mcr Genes in Thailand, 2016–2019 - Paveenkittiporn, Wantana; Kamjumphol, Watcharaporn; Ungcharoen, Ratchadaporn; Kerdsin, Anusak (Frontiers in Microbiology, 2021)
Mobile colistin-resistant genes (mcr) have become an increasing public health concern. Since the first report of mcr-1 in Thailand in 2016, perspective surveillance was conducted to explore the genomic characteristics of clinical carbapenem-resistant Enterobacterales (CRE) isolates harboring mcr in 2016–2019. Thirteen (0.28%) out of 4,516 CRE isolates were found to carry mcr genes, including 69.2% (9/13) of E. coli and 30.8% (4/13) of K. pneumoniae isolates. Individual mcr-1.1 was detected in eight E. coli (61.5%) isolates, whereas the co-occurrence of mcr-1.1 and mcr-3.5 was seen in only one E. coli isolate (7.7%). No CRE were detected carrying mcr-2, mcr-4, or mcr-5 through to mcr-9. Analysis of plasmid replicon types carrying mcr revealed that IncX4 was the most common (61.5%; 8/13), followed by IncI2 (15.4%; 2/13). The minimum inhibitory concentration values for colistin were in the range of 4–16 µg/ml for all CRE isolates harboring mcr, suggesting they have 100% colistin resistance. Clermont phylotyping of nine mcr-harboring carbapenem-resistant E. coli isolates demonstrated phylogroup C was predominant in ST410. In contrast, ST336 belonged to CC17, and the KL type 25 was predominant in carbapenem-resistant K. pneumoniae isolates. This report provides a comprehensive insight into the prevalence of mcr-carrying CRE from patients in Thailand. The information highlights the importance of strengthening official active surveillance efforts to detect, control, and prevent mcr-harboring CRE and the need for rational drug use in all sectors.